Ideographic Reconstruction of the Nominative Set “Fundamentals of Power Relations in the State» - L. Guo; A. V. Shchetinina (Научный диалог)
The nominative set “Fundamentals of power relations in the state”, structured using the method of ideographic reconstruction, is considered. The relevance of the study is due to the lack of a comprehensive ideographic description of the socio-political vocabulary of the Russian language and the need for the planned development of each of its sectors. It is noted that the ideographic reconstruction of nominative sets that combine lexemes and idiomatic expressions makes it possible to systematically describe fragments of reality: relations in the state, society, between individuals - in the form of frame constructions that reproduce the scheme of actions in real life. The language units for the study were extracted from modern and historical explanatory dictionaries of the Russian language, fixing vocabulary from the 11th to the 21st centuries. It is shown that the ideographic grid “Fundamentals of power relations in the state” is organized in the form of a “ladder” of ideograms, the levels of which (43 slots) reflect the branches of semantic subordination between groups of synonymous units that form series within each ideogram. The ideograms of the nuclear and circumnuclear zones, as well as those located on the near and far periphery are described. It is indicated that this field unites more than 1400 units: modern and obsolete tokens and idiomatic expressions. The conclusion is drawn about the scientific and methodological significance of the ideographic description of vocabulary in the aspect of studying both Russian and foreign languages.